2019
DOI: 10.1186/s13075-019-1869-z
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of bariatric surgery on outcomes in rheumatic diseases

Abstract: Obesity is associated with numerous comorbidities including some rheumatic conditions. Through adipose-derived inflammation, obesity has been shown to induce increased initiation, progression, and worse responses on outcomes of rheumatic diseases. Bariatric surgery is being increasingly used thanks to its positive effects on major comorbidities such as type 2 diabetes mellitus and hypertension. Consequently, surgically induced weight and adipose tissue losses might play a role in the course of rheumatic condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…The larger number of cohort studies in the present analysis contributed to more precise risk estimates, and enabled assessment of associations of other adiposity measures, such as waist circumference and BMI in early adulthood, with risk of rheumatoid arthritis. Some studies have suggested that bariatric surgery may improve symptoms in patients with rheumatoid arthritis 40,41 , however, www.nature.com/scientificreports/ a recent Swedish study found no significant association between bariatric surgery and the risk of developing rheumatoid arthritis (HR = 0.92, 95% CI 0.59-1.46), but statistical power to detect a moderate association may have been low and confidence intervals were wide 42 . The finding that high BMI in early adulthood (at age 18 years) was associated with an increased risk of rheumatoid arthritis might suggest that early life risk factors may be of importance in the aetiology of rheumatoid arthritis 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…The larger number of cohort studies in the present analysis contributed to more precise risk estimates, and enabled assessment of associations of other adiposity measures, such as waist circumference and BMI in early adulthood, with risk of rheumatoid arthritis. Some studies have suggested that bariatric surgery may improve symptoms in patients with rheumatoid arthritis 40,41 , however, www.nature.com/scientificreports/ a recent Swedish study found no significant association between bariatric surgery and the risk of developing rheumatoid arthritis (HR = 0.92, 95% CI 0.59-1.46), but statistical power to detect a moderate association may have been low and confidence intervals were wide 42 . The finding that high BMI in early adulthood (at age 18 years) was associated with an increased risk of rheumatoid arthritis might suggest that early life risk factors may be of importance in the aetiology of rheumatoid arthritis 43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Obesity increases a risk of osteoarthritis and in turn the need for joint replacement arthroplasty [ 15 ]. Bariatric surgery could reduce that risk, but studies also found an increased risk of fracture after surgery [ 16 , 17 ], osteoporosis [ 18 ] and generalized bone pain due to impaired absorption of vitamin D and calcium [ 19 ]. Patients struggling with this dilemma should be informed about the pros and cons, including the uncertainty of long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Non-surgical weight loss interventions contributed to a weight loss of 4.5 kg and significantly improved physical function in 19 overweight RA patients 26 . Furthermore, a more substantial strategy for weight loss, such as surgery, also has an impact on the levels of various inflammatory markers induced by obesity [27][28][29][30] . Santos et al 31 enrolled 46 patients with obesity-related metabolic dysfunction and showed that gastric banding surgery resulted in a significant decrease in the inflammation process associated with adipose tissue loss.…”
Section: Discussionmentioning
confidence: 99%